A STUDY ON CONSUMER CONVENIENCE STRATEGIES FOR SHOPPING MALL LOYALTY AT TANJAVOOR - Narmatha, D.; Swaminathan, Dr. R (IJRDO - Journal of Business Management, 2017)
Shopping malls have seen an impressive growth in India during the past few decades. However, the malls have not been able to consistently provide a one stop destination to the consumers in Tanjavoor this paper examines the attractiveness factors of shopping malls from the shoppers’ perspective based on the survey of urban shoppers. There are three malls taken into consideration in this study which represent the city of Tanjavoor in a geographical manner. This paper proposes to study the shopping mall attractiveness wherein the attempt is to study the behavior and attitude of the shoppers towards malls. Furthermore, the paper also proposes to derive the constituents of an ideal mall from shopper’s perspective. This study revealed six attitude factors of the shoppers towards malls: Locality & Convenience, Relaxed Shopping, Prestige Shopping, Product knowledge, Any day visit and Price Parity. The study also arrived at characteristics of a mall that people consider while visiting the mall which are Overall Attractiveness, Amenities & Atmospherics, Personnel, Shopping Ease and Convenience. The categorization of attractiveness factors for studying the behavior and attitude of the shoppers towards malls reveal the overall insight about the concept of an ideal mall and therefore, allow the mall managers to develop effective retail strategies to deliver the desired values